Hyperbranched alkyd/magnetite-silica nanocomposite as a coating material. (5th December 2017) - Selim, Mohamed S.; Wang, Feng Q.; Yang, Hui; Huang, Yong; Kuga, Shigenori
Abstract: Engineering innovative nanomaterials with low volatile organic content (VOC) has awarded great interest to control air pollutant emissions. We designed a highly branched alkyd matrix suitable for surface coating from castor oil via polyesterification. A simple A2 + B3 (di- and tri-functional monomers) methodology was used to prepare the hyperbranched polyester from natural multifunctional monomers. Magnetite-coated silica (Fe3 O4 @SiO2 ) particles with 60–70 nm average diameter were prepared by in situ method that binds magnetite nanoparticles to silica nanospheres. The magnetite size and attaching efficiency were controlled by the concentration of chemicals and reflux duration. The nanocomposite coating was prepared by solution casting. The structure-property relationship was studied for different concentrations of nanofiller in the alkyd matrix. The surface and anticorrosive properties were studied via contact angle and salt spray tests. Mechanical performance and thermal stability were assessed by various methods. The highest improvement was achieved with nanofiller insertion up to 0.5% Fe3 O4 @SiO2 nanospheres. Graphical abstract: Highlights: A conformal series of castor oil based hyperbranched Alkyd/Fe3 O4 @SiO2 nanocomposites was developed as a coating material. Structure-property relationship was studied by incorporating different nanofiller concentrations in the alkyd matrix. Shape and size control of nano-Fe3 O4 @SiO2 is crucial to achieve well-dispersed nanospheres with good filler properties. Well-dispersed nanoparticles (especially 0.5%) in alkyd matrix exerted improved mechanical and anticorrosive properties.